Upaya Meningkatkan Minat dan Hasil Belajar Matematika Materi Luas Bangun Ruang dengan Media Bangun Ruang pada Siswa Kelas VI SD Negeri 002 Bengkong Semester 2 Tahun Pelajaran 2021/2022 - Umi Kalsum (Journal on Education, 2022)
This research is a Classroom Action Research (CAR) which aims to find out how to increase interest and learning outcomes in mathematics on the subject of spatial construction using the media for the sixth grade students of SD Negeri 002 Bengkong in the second semester of the 2021/2022 academic year. The results showed that students who had learning outcomes in the high category increased from 20 students who completed to 30 who completed the second cycle. In addition, student learning outcomes also increased, where in the pre-cycle when learning was not implemented using spatial media from the first cycle, the average value was 71.34 to 78.95. The percentage of students who finished studying was 55.26% in the first cycle then in the second cycle rose to 78.95%. So with the acquisition of these numbers, the application of spatial media meets the successful category, because it has met the predetermined success rate, which is 75%.